2016
DOI: 10.1111/crj.12584
|View full text |Cite
|
Sign up to set email alerts
|

Increased lysyl oxidase‐like 2 associates with a poor prognosis in non‐small cell lung cancer

Abstract: These results demonstrate that elevated LOXL2 levels are positively associated with poor prognosis in NSCLC patients. LOXL2 might, therefore, serve as a novel prognostic biomarker and potential therapeutic target in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…It was found that LOXL2 was significantly overexpressed in NSCLC samples compared to normal tissues; cytoplasmic and nuclear LOXL2 were negligible in healthy lung tissue whereas, in NSCLC specimens, LOXL2 levels were elevated. Furthermore, this increased level of LOXL2 was associated with an increase in tumor size and stage of cancer in adenocarcinoma and squamous cell carcinoma subgroups . This is further supported by silencing of LOXL2, inhibited migration, and invasion in lung squamous cell carcinoma cell lines…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 52%
See 2 more Smart Citations
“…It was found that LOXL2 was significantly overexpressed in NSCLC samples compared to normal tissues; cytoplasmic and nuclear LOXL2 were negligible in healthy lung tissue whereas, in NSCLC specimens, LOXL2 levels were elevated. Furthermore, this increased level of LOXL2 was associated with an increase in tumor size and stage of cancer in adenocarcinoma and squamous cell carcinoma subgroups . This is further supported by silencing of LOXL2, inhibited migration, and invasion in lung squamous cell carcinoma cell lines…”
Section: Is Loxl2 a Viable Cancer Target?mentioning
confidence: 52%
“…Furthermore, this increased level of LOXL2 was associated with an increase in tumor size and stage of cancer in adenocarcinoma and squamous cell carcinoma subgroups. [96] This is further supported by silencing of LOXL2, inhibited migration, and invasion in lung squamous cell carcinoma cell lines. [97] Investigations into the underlying mechanism involved in tumor progression in NSCLC have uncovered endogenous miRNA's (mi-Rs) to be directly involved in LOXL2 expression.…”
Section: Lung Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…The samples were then independently analyzed by two pathologists who did not have any clinical information about the patients. The scores for protein expression were determined as previously described (14,15). Staining intensity was scored as the following: 0 (negative), 1 (weak), 2 (medium) or 3 (strong).…”
Section: Immunohistochemical Staining and Scoring In Tmasmentioning
confidence: 99%
“…In all the kinds of lung cancers, NSCLC accounts for about 80%, and the 5-year overall survival rate of NSCLC is only 15.9% . Histologically, NSCLC is further comprised of adenocarcinoma (AC) and squamous cell carcinoma (SCC), accounting for approximately 40% and 25%-30% of all lung cancers, respectively (Zhan et al 2016). …”
Section: Introductionmentioning
confidence: 99%